LITHUANIA’S ECONOMIC DEVELOPMENT DURING EU MEMBERSHIP - KUOKŠTIS, VYTAUTAS (Politologija, 2015)
This article surveys the Lithuanian economic experience related to its membership in the European Union. It provides an overview of short and medium-term macroeconomic trends as well as issues related to long-term economic development. This article reveals that the Lithuanian economy was highly volatile during the period analysed. After very fast expansion in the wake of the EU accession, the country encountered a very severe economic crisis in 2008–2010. At the same time, it must be noted that Lithuania was the most successful new EU member state in terms of economic convergence, at least when looking at how much it reduced the gap between its GDP per capita and the EU average. This article also looks at changes in the Lithuanian economic integration within the EU. It finds that economic integration in 2004–2014 increased fast in the areas of trade, investments and labour mobility in absolute terms. At the same time, the relative share of trade with EU member states declined.This article also aims to provide a discussion on the EU’s causal influence on the Lithuanian economy. It highlights the issues and complications related to such an evaluation which requires the formulation of a proper counterfactual. To this end, several potential channels of the EU’s influence are analysed. Based on economic theory and literature overview of concrete impact assessments, this article concludes that the membership’s impact was substantial and positive. In terms of different impact channels, increased trade integration, higher foreign direct investments as well as a solidified favourable institutional environment were unequivocally beneficial. At the same time, there were also some negative aspects, primarily related to higher labour mobility which contributed to economic “overheating” prior to the crisis and raises concerns about future growth prospects.